The Challenges Faced by the Model Teachers in Implementing Lesson Study - Sri Damayanti (Universitas Cokroaminoto Palopo, 2019)
Previous studies have shown that the implementation of Lesson Study can give a good impact on both teachers and students. Lesson Study can help them binding up as a Learning Community in order to improve their self-development in teaching and learning. In addition, teachers and students prefer Lesson Study to be a sustainable activity in school. However, although Lesson Study has given a positive value on its practices, it does not mean that there are no challenges. The main purpose of this study is trying to reveal the challenges faced by the model teacher while implementing of Lesson Study practices. This study was a descriptive study, where the data were collected by interviewing 11 model teachers who teach in four different schools. The interview is given after conducting Lesson Study practices that cover three phases: PLAN, DO and SEE. The findings reveal that most of the model teachers faced challenges in PLAN phase and DO phase. In PLAN phase, model teachers stated that they find it difficult to develop Chapter Design because they did not understand well how to put their idea. They also find it difficult to adapt what they have written in Chapter Design and their activity when doing Open Class. In DO phase, most of model teachers stated that basically Lesson Study has a big impact in increasing their students’ understanding about learning materials, but the students were not active enough in the teaching and learning process. It means that the model teachers have to do a bigger effort to make their students more active in the classroom activities.